Shared Encounters - Willis, Katharine S.; Roussos, George; Chorianopoulos, Konstantinos; Struppek, Mirjam (Shared Encounters, 2009)
The approach often adopted by Human Computer Interaction (HCI) focuses on exchanges between a person and the interface of a device situated within a specific context of use. This view is increasingly challenged by the complex and dynamic world of the physical and social environment integrated with ubiquitous technologies, which requires an alternative view that sees people creating settings which frame and structure their encounters. As a result, in recent years, HCI researchers have recognized the need for social and physical data to be gathered and interpreted, but have often been frustrated in their attempts to codify and make sense of the complex and dynamic nature of the real world of human experience. Developments in the early 90s such as the emergence of the field of Computer Supported Cooperative Work (CSCW), the introduction of the concept of social navigation (Hook et al. 2003), work on ambient environments, the UbiComp conference series as well as more theoretical positions on embodied or situated interaction (Dourish 2001, McCullough 2005) have all lead the way to a new understanding of HCI. Another driver for this change in emphasis in HCI is the emergence of mobile and ubiquitous computing that has brought significant changes in social and cultural practices in spatial settings. Interactions through and with ubiquitous technologies no longer require physical co-presence and have broadened the range of possible interactions as well as the range of settings in which these interactions can unfold. The basis for this lies in the fact that physical distance no longer prevents many of the types of interactions and encounters that had previously been confined to face-to-face contact. As a result, there has been much discussion on the role of spatial setting and interaction mediated through technologies such as that on the role of space and agency in the quality of the interaction (Dourish and Harrisson 1996) and also the broader concept of the situated behavior and actions (Suchman 1987). A good deal has also been written on the subject of social collaboration among individuals using communication devices and the conditions or features that are required to enable such activities (Gaver 1992; Paulos and Goodman 2004; Hook et al. 2003; Churchill et al. 2004). Further discussion has focused on the technologies themselves, assessing the social impact of the emerging forms of behavior, such as the activities of ad hoc communities enabled through mobile technologies (Rheingold 2002), or the patterns of mobile phones’ use (Katz and Aakhus 2002). Finally, numerous applications and locative media projects (e.g., Harle and Hopper 2005) which explore interactions through realization have been developed. These projects and research offer many useful insights, but there still remain many questions about how to create the conditions for meaningful and persisting shared interactions in public space. The challenge is not only to build systems that respond to rich and dynamic social and physical events, but also to provide a structure for sustainable participation and sharing.